2009
DOI: 10.1111/j.1750-3639.2008.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

SJL Mice Exposed to Cuprizone Intoxication Reveal Strain and Gender Pattern Differences in Demyelination

Abstract: The role of mouse strain and the influence of gender on demyelination were explored for the first time in SJL mice using the cuprizone intoxication model. We document here that SJL mice display a unique pattern of demyelination that did not follow the profile that is well-characterized in C57BL/6 mice. The SJL mice did not readily demyelinate at the midline within the corpus callosum but showed greater demyelination immediately lateral to midline. During continuous exposure to cuprizone, demyelination was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 52 publications
(82 reference statements)
4
61
1
Order By: Relevance
“…In regard to sex differences in demyelination and remyelination, Patel et al (2013) found that cuprizone feeding to C57BL/6 mice leads to a greater loss of conductivity of neurons in the corpus callosum in males than in females; however, the extent of demyelination or remyelination was not different between the sexes as measured by myelin basic protein immunohistochemistry. Slightly different results have been reported for the SJL strain where this same cuprizone-feeding regimen resulted in more severe demyelination in male than in female mice (Taylor et al 2009). However, again no differences in the extent of remyelination were observed between the sexes (Taylor et al 2009).…”
Section: Demyelination/remyelinationmentioning
confidence: 91%
See 2 more Smart Citations
“…In regard to sex differences in demyelination and remyelination, Patel et al (2013) found that cuprizone feeding to C57BL/6 mice leads to a greater loss of conductivity of neurons in the corpus callosum in males than in females; however, the extent of demyelination or remyelination was not different between the sexes as measured by myelin basic protein immunohistochemistry. Slightly different results have been reported for the SJL strain where this same cuprizone-feeding regimen resulted in more severe demyelination in male than in female mice (Taylor et al 2009). However, again no differences in the extent of remyelination were observed between the sexes (Taylor et al 2009).…”
Section: Demyelination/remyelinationmentioning
confidence: 91%
“…Slightly different results have been reported for the SJL strain where this same cuprizone-feeding regimen resulted in more severe demyelination in male than in female mice (Taylor et al 2009). However, again no differences in the extent of remyelination were observed between the sexes (Taylor et al 2009). Another study in rats that evaluated sex differences in remyelination after ethidium bromide injection into cerebellar peduncles found that while the rate of remyelination was similar between the sexes in young rats, it was less efficient in middle 12-month (aged) rats, particularly in males (Li et al 2006b).…”
Section: Demyelination/remyelinationmentioning
confidence: 91%
See 1 more Smart Citation
“…A number of reports have indicated that this demyelination model also displays abnormal behaviors and cognitive defects that are believed to be a direct result of demyelination [28,29,37,38] . The behavior changes may reflect neuronal abnormalities, like anxiety and cognitive impairment, and mimic, at least partially, schizophrenia symptoms in humans.…”
Section: Resultsmentioning
confidence: 99%
“…The pathological features of both EAE and cuprizone vary according to the species, strain and antigen used [44,45] ; gender and age also influence the response to cuprizone [45,46] . EAE is a model of CNS inflammatory demyelination, induced by inoculation with various CNS myelin antigens or passive transfer of myelin-specific T cells.…”
Section: Eae and Cuprizone Models Of Multiple Sclerosismentioning
confidence: 99%